Sensitivity of urine-grown cells of Providencia stuartii to antiseptics. Issue 10 (October 1978) - Thomas, B; Sykes, L; Stickler, D J
Abstract : Urine-grown cultures of 23 clinical isolates of Gram-negative bacteria having a range of minimum inhibitory concentration values for chorhexidine were challenged with various concentrations of this antiseptic. The results suggest that cells of Providencia stuartii, in particular, exhibit a considerable degree of resistance to chlorhexidine under these conditions, concentrations of up to 10 000–20 000 microgram/ml of urine being necessary to produce complete loss of viability of such cultures. Of the other two antiseptics tested, phenoxyethanol proved to be the more effective, the recommended use concentration of 2% v/v producing reductions in viable counts of greater than six logarithms in all the strains examined. It is suggested that phenoxyethanol may be a suitable alternative to the cationic agents for use in antiseptic policies for bladder management of urinary tract infections with Providencia stuartii.